2021
DOI: 10.3350/cmh.2020.0333
|View full text |Cite
|
Sign up to set email alerts
|

Serum fibrosis index-based risk score predicts hepatocellular carcinoma in untreated patients with chronic hepatitis B

Abstract: were responsible for the acquisition and analysis of data, had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. All authors were responsible for the interpretation of data, the drafting, and critical revision of the manuscript for important intellectual content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
1
19
2
Order By: Relevance
“…Although baseline characteristics in this study 6 , such as old age, higher cirrhosis rates, and similar serum HBV DNA levels, showed a higher risk of HCC development compared with those in previous studies, 4,5 the risk of HCC development was quite lower than that in previous studies. The 5-year risk of HCC development was only 0.19% in the low-risk group and 1.12% in the high-risk group according to the Liang scores 6 . Even in the high-risk group, the HCC risk in this study was still lower than that mentioned in the previous studies.…”
contrasting
confidence: 70%
See 4 more Smart Citations
“…Although baseline characteristics in this study 6 , such as old age, higher cirrhosis rates, and similar serum HBV DNA levels, showed a higher risk of HCC development compared with those in previous studies, 4,5 the risk of HCC development was quite lower than that in previous studies. The 5-year risk of HCC development was only 0.19% in the low-risk group and 1.12% in the high-risk group according to the Liang scores 6 . Even in the high-risk group, the HCC risk in this study was still lower than that mentioned in the previous studies.…”
contrasting
confidence: 70%
“…In this study, 15,187 patients who had a median age of 51.9 years, had a median HBV DNA levels of 4.4 log 10 IU/mL, and of whom 5.4% had cirrhosis, only 1.2% developed HCC during a mean follow-up of 52 months. Although baseline characteristics in this study [ 6 ], such as old age, higher cirrhosis rates, and similar serum HBV DNA levels, showed a higher risk of HCC development compared with those in previous studies [ 4 , 5 ], the risk of HCC development was quite lower than that in previous studies. The 5-year risk of HCC development was only 0.19% in the low-risk group and 1.12% in the high-risk group according to the Liang scores [ 6 ].…”
contrasting
confidence: 60%
See 3 more Smart Citations